Ovarian tumor: Rare presentation of breast cancer metastasis - Mahno, Noor Ezmas; Idris, Mohd Faiz; Amjad, Nasseer (2014)
Introduction: Ovarian metastasis is uncommon. Approximately, 10% breast carcinoma will have ovarian involvement1 . It involved bilateral ovaries in about 80% of cases 1 . Due to its low prevalence, ovarian metastasis from a lobular type of breast carcinoma is rare. Here, we presented a case of invasive lobular breast carcinoma metastasis to ovaries after 6 years of the first diagnosis Case Summary: This is a 39 years old Malay lady diagnosed as left breast invasive lobular carcinoma with initial clinical staging of T2 N1 M0 in 2008. Initially she had wide local excision with axillary clearance but due to involved deep surgical margin she underwent mastectomy. Progestrogen receptor is positive. Estrogen and HER2 receptor was negative. Subsequently, she completed FAC regimes and radiotherapy. She has been on Tamoxifen since 2010. In January 2014, she presented with painless abdominal distension of 4 months duration without bowel or urinary symptom or pain. CT scan showed bilateral ovarian masses, likely malignant. Exploratory laparotomy was carried out by the Gynaecology team. Intraoperatively, there was bilateral ovarian tumor with pelvic lymphadenopathy and ascites. Total abdominal hysterectomy bilateral salphingoophorectomy and omentectomy was done. Histopathological reports came back as metastatic ovarian invasive lobular carcinoma with positive pelvic lymphadenopathy but no omentum involvement. After oncologist consultation, we planned for second line of chemotherapy, Doxitacel for 6 cycles.